2023
DOI: 10.1021/acs.orglett.2c04234
|View full text |Cite
|
Sign up to set email alerts
|

Silver-Catalyzed Direct Nucleophilic Cyclization: Enantioselective De Novo Synthesis of C–C Axially Chiral 2-Arylindoles

Abstract: Atropisomeric indoles widely exist in natural products, pharmaceuticals, functional materials, and catalysts for their featured biological activities, photoelectric properties, and catalytic activities, while facile and de novo construction of this motif remains underexplored. Herein, we report a chiral silver phosphatecatalyzed direct 5-endo-dig nucleophilic cyclization of 2-alkynylanilins under mild conditions, affording various C−C axially chiral 2arylindoles in high to excellent yields and enantioselectivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…The scope of the atroposelective synthesis was examined with substituted diarylacetylenes 11a–u with different sulfonamide groups using the optimal two catalysts B and S′ , which allow accessing enantiodivergently ( R )- or ( S )-2-arylindoles 12 , respectively (Scheme ). The absolute configuration of all products was based on those of ( R )- 12a and ( R )- 12l , whose configuration was assigned by X-ray diffraction, as well as by comparison of the optical rotation of the enantioenriched arylindoles with the literature data . Moderate to good enantioselectivities were observed in all cases, with the exception of 12t and 12u , which were obtained as nearly racemic mixtures, most probably due to the lower size of 2-methylnaphthalene in 12t and benzo­[ d ]­[1,3]­dioxole in 12u .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The scope of the atroposelective synthesis was examined with substituted diarylacetylenes 11a–u with different sulfonamide groups using the optimal two catalysts B and S′ , which allow accessing enantiodivergently ( R )- or ( S )-2-arylindoles 12 , respectively (Scheme ). The absolute configuration of all products was based on those of ( R )- 12a and ( R )- 12l , whose configuration was assigned by X-ray diffraction, as well as by comparison of the optical rotation of the enantioenriched arylindoles with the literature data . Moderate to good enantioselectivities were observed in all cases, with the exception of 12t and 12u , which were obtained as nearly racemic mixtures, most probably due to the lower size of 2-methylnaphthalene in 12t and benzo­[ d ]­[1,3]­dioxole in 12u .…”
Section: Resultsmentioning
confidence: 99%
“…63 An organocatalytic synthesis of axially chiral naphthyl-C 2 -indoles via cyclization of ortho-alkynoanilines using a quinine-derived thiourea catalyst has been reported. 64 More recently, the Pdcatalyzed Cacchi reaction 65 and a chiral silver phosphatecatalyzed cyclization 66 Our study commenced by testing selected chiral gold(I) complexes based on variations of our original design (Figure 1) in the cyclization of sulfonamide 11a to give 2-arylindole 12a (Table 1). Initial screening of silver salts showed that AgNTf 2 was optimal for the reaction.…”
Section: Atroposelective Synthesis Of Indolesmentioning
confidence: 99%
“…Control experiments implied the possibility of cooperative catalysis ( TS ‐ 10 ), in which AgOAc accelerated the required conversion while CPA improved the enantioselectivity (Scheme 28). [50] …”
Section: Asymmetric Cyclization Synthesis Of Heterobiarylsmentioning
confidence: 99%
“…Enantioselective de novo synthesis of axially chiral 2arylindoles. [50] time. Then, vicinal diimine intermediate Int-51 is generated by releasing a molecule of water.…”
Section: Intermolecular Cyclizationmentioning
confidence: 99%
“…Very recently in 2023 Zhao and coworkers explored a facile enantioselective de novo fabrication of atropisomeric indoles 87 . 75 They fabricated these synthetically potent axially chiral indoles via direct nucleophilic 5- endo-dig cyclization using AgOAc 19 /chiral phosphoric acid (Fig. 5) dual catalytic system 86 .…”
Section: Classificationmentioning
confidence: 99%